Caribbean basin trade and investment guide - Power, Kevin P. (Washington International Press Washington DCUS, 1984)
Provides a central source of information for the businessman interested in investigating business opportunities in the Caribbean and Central America. Gives twenty five country profiles which include information on the history, political system, and economy of each territory. Profiles also contain information on investment incentives, taxation, labour, export incentives, and sources of further information. Lists a number of Regional Organizations, Multilateral Institutions, U.S Government Agencies, and Private Organizations that offer further business information and assistance. Outlines incentives offered by free zones in Caribbean. Discusses shipping and insurance in Caribbean and describes trade programs in the US, EEC, and Canada.